Polyandry Marriage in Criminal Law Studies in Indonesia - Asmuni Asmuni; Pagar Pagar; Maswandi Maswandi (Budapest International Research and Critics University, 2020)
This study discusses polyandry marriage in criminal law studies in Indonesia. In terms of marriage, there are still some Muslim women who violate Islamic law, either secretly who will carry out further marriages even though they are still married to other men (polyandry marriage), even though both are in the Qu’ran and Hadith which prohibits this act because it is an act of adultery with the threat of positive punishment as regulated in the Criminal Law Number 1 of 1946 and the Islamic Criminal Law. Because this polyandry marriage does not only involve the perpetrator but also other parties so that the marriage is carried out, the criminal arrangements in the Criminal Code related to polyandry marriage can be punishable with a sentence ranging from 9 months to 7 years in prison. In fact, polyandry marriage according to the Qoran and Hadith can be subject to death penalty, death penalty 100 times or imprisonment for 1 year.